Preparation method of wide-temperature-range lithium ion battery diaphragm
By using covalent organic frame material Tp-BD-COF with polyethylene and liquid paraffin to prepare the separator, the problems of low conductivity and low specific capacity of commercial PP separators in the low temperature zone are solved, and lithium-ion batteries are realized at low temperatures The good performance and high specific capacity improve the safety and production convenience of the battery.
Patent Information
- Application Number
- CN202411309821.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-19
- Publication Date
- 2024-12-24
AI Technical Summary
The existing commercial PP diaphragms have low conductivity in the low temperature zone, and the assembled batteries have low specific capacity in the wide temperature zone, which affects the performance and safety of lithium-ion batteries.
The separator was prepared by rolling method using covalent organic frame material Tp-BD-COF, polyethylene (PE) and liquid paraffin to form an activated Tp-BD-COF separator, and applied it to the lithium-ion battery separator. Optimize process flow to improve ion conductivity and battery performance.
It achieves good battery performance and high specific capacity in a wide temperature zone, improves the safety performance of the battery, simplifies the process flow, and is suitable for large-scale production.
Smart Images

Figure CN119176966A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of new energy materials, and specifically relates to a method for preparing a wide-temperature range lithium-ion battery separator. Background Art
[0002] With the development of new energy, rechargeable lithium batteries have become one of the most suitable energy storage systems in our electrified society. From smartphones to electric vehicles, lithium batteries have been widely used in various electronic devices. However, the growth of lithium dendrites seriously affects the safety and cycle performance of lithium metal batteries (LMBs). In addition, low temperature has a great impact on battery performance. At a temperature of -15℃, the discharge capacity of the battery at C / 5 rate will be 80% of the nominal capacity.
[0003] Covalent organic framework materials have always been a research hotspot for the next generation of sustainable lithium-ion batteries (LIBs). Covalent organic frameworks (COFs) are a new type of crystalline porous polymers with high specific surface area, long-range ordered structure and functionalization. In particular, imides have attracted much attention due to their advantages such as low cost, fast redox reaction and good environmental benefits. However, the conductivity of existing commercial PP separators will be greatly reduced in low temperature areas, and the specific capacity of batteries assembled with commercial PP separators is also low in a wide temperature range. Summary of the invention
[0004] In order to overcome the shortcomings of the prior art and solve technical problems such as low conductivity of existing commercial PP separators in low temperature zones and low specific capacity of assembled batteries in wide temperature zones, the present invention provides a method for preparing a wide temperature range lithium-ion battery separator.
[0005] The present invention is achieved through the following technical solutions.
[0006] The present invention provides a method for preparing a wide temperature range lithium ion battery separator, comprising the following steps:
[0007] 1) Preparation of covalent organic framework material Tp-BD-COF;
[0008] 2) Preparation of Tp-BD-COF membrane:
[0009] The covalent organic framework material Tp-BD-COF prepared in step 1) is placed at 120° C. for 12 hours for activation to obtain activated Tp-BD-COF;
[0010] Weigh the activated Tp-BD-COF and PE and grind them evenly, then continue to add liquid paraffin and mix well; place the mixed materials at 140-160°C until PE melts and then stand for 20-30 seconds, and take them out after the mixture is formed;
[0011] The mixture was placed on a roller press and the temperature was controlled at 110-115° C. to roll into a diaphragm with a thickness of 10-40 μm, the diaphragm was immersed in dichloromethane for 12 hours, and then the diaphragm was placed in a 60° C. oven for drying, and finally the diaphragm was cut into a circular diaphragm using a cutting machine to obtain a Tp-BD-COF diaphragm;
[0012] 3) Assemble button batteries;
[0013] 4) Test the performance of button batteries.
[0014] Furthermore, the step of preparing the covalent organic framework material Tp-BD-COF in step 1) is as follows: weighing trialdehyde phloroglucinol and benzidine into an ampoule tube and adding anisole and acetic acid solution in sequence, degassing by freeze-thaw cycle in a liquid nitrogen environment, sealing the ampoule tube and placing it in a constant temperature oven at 110-130°C to react for 90-100h to obtain the covalent organic framework material Tp-BD-COF.
[0015] Furthermore, in the step 1), the molar ratio of trialdehyde phloroglucinol, benzidine, anisole and acetic acid solution is 0.05-0.2: 0.075-0.3: 1.5-3: 0.1-0.3.
[0016] Furthermore, the concentration of the acetic acid solution in step 1) is 12 mol / L.
[0017] Furthermore, in the step 2), the mass ratio of activated Tp-BD-COF, PE and liquid paraffin is 5-9:1-5:1.
[0018] Furthermore, in the step 2), the mass ratio of activated Tp-BD-COF, PE and liquid paraffin is 8:2:1.
[0019] Furthermore, in the step 2), the temperature of PE when it is melted is controlled at 150° C., and the temperature of the roller press is controlled at 112° C. and the roller press is performed five times to form a diaphragm with a thickness of 25 μm.
[0020] Furthermore, the diameter of the circular diaphragm in step 2) is 9 mm.
[0021] Furthermore, the step of assembling the button battery in step 3) is: coating the active material, binder and conductive agent in a ratio of 8:1:1, placing in a vacuum oven to maintain 100-140°C for drying and cutting to obtain lithium iron phosphate pole pieces, assembling the Tp-BD-COF diaphragm and lithium iron phosphate pole pieces obtained in step 2) in the button battery to obtain a lithium-ion battery.
[0022] Furthermore, in the step 3), the active material is lithium iron phosphate, the binder is polyvinylidene fluoride, and the conductive agent is carbon black.
[0023] The beneficial effects achieved by the present invention are as follows: the present invention selects a covalent organic framework material Tp-BD-COF and PE to prepare a Tp-BD-COF diaphragm through a roller pressing method and applies it to the field of lithium ion battery diaphragms; the roller pressing method is simple in preparation and convenient in process flow; the pore effect of the covalent organic framework material Tp-BD-COF is used to prepare a diaphragm with good ion conductivity; and a button battery assembled using the Tp-BD-COF diaphragm has a stable charge and discharge curve and still has good performance at low temperatures compared to a commercial PP diaphragm; the conductivity and the specific capacity of the assembled battery in a wide temperature range are both better than those of the commercial PP diaphragm; the safety performance is high and it is easy to mass produce.
[0024] Compared with the prior art, the present invention has the advantages of simple preparation method, convenient process flow, high safety performance, high conductivity of Tp-BD-COF diaphragm, high specific capacity of assembled battery in a wide temperature range, and easy large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 This is a structural diagram of the covalent organic framework material Tp-BD-COF of the present invention;
[0026] Figure 2 It is an X-ray powder diffraction pattern of the covalent organic framework material Tp-BD-COF of the present invention;
[0027] Figure 3 Schematic diagram of the Tp-BD-COF membrane of the present invention;
[0028] Figure 4 is a diagram of the symmetric battery conductivity value of the Tp-BD-COF separator in Example 3 of the present invention;
[0029] Figure 5 : is a charge and discharge curve diagram of a button battery in Example 3 of the present invention at different temperatures;
[0030] Figure 6 It is a performance diagram of different temperature cycles of the button battery in Example 3 of the present invention. DETAILED DESCRIPTION
[0031] The present invention is further described in detail below in conjunction with the accompanying drawings and embodiments.
[0032] Example 1
[0033] like Figures 1 to 6 As shown, a method for preparing a wide temperature range lithium-ion battery separator comprises the following steps:
[0034] 1) Preparation of covalent organic framework material Tp-BD-COF:
[0035] 0.01mmol of trialdehyde phloroglucinol and 0.15mmol of benzidine were weighed into an ampoule tube, and 2ml of anisole and 0.2ml of acetic acid solution were added in sequence. The ampoule tube was degassed by freeze-thaw cycles for 3 times under liquid nitrogen environment. The ampoule tube was sealed and placed in a constant temperature oven at 120℃ for 96h to obtain an orange covalent organic framework material Tp-BD-COF. Figure 1 This is the structural diagram of the prepared covalent organic framework material Tp-BD-COF, wherein the concentration of the acetic acid solution is 12 mol / L;
[0036] 2) Preparation of Tp-BD-COF membrane:
[0037] The covalent organic framework material Tp-BD-COF prepared in step 1) is placed at 120° C. for 12 hours for activation to obtain activated Tp-BD-COF;
[0038] Weigh 6 mg of activated Tp-BD-COF and 4 mg of PE and grind them evenly. Grind the white PE particles and the orange-yellow activated Tp-BD-COF until there is no obvious granularity, then add 1 mg of liquid paraffin and mix well. Place the mixed material at 150°C until the PE melts and then stand for 20-30 seconds. Take it out after the mixture is formed.
[0039] The mixture was placed on a roller press and the temperature was controlled at 112°C to roll to a 25 μm thick membrane. The membrane was then rolled five times to soak in dichloromethane for 12 hours to remove the liquid paraffin. The membrane was then placed in a 60°C oven for 1 hour to dry to remove the dichloromethane. Finally, the membrane was cut into 9 mm round membranes using a cutting machine to obtain a Tp-BD-COF membrane. Figure 3 , the mass is 10-14 mg; the roller pressing method is simple and the process flow is convenient;
[0040] 3) Assemble the button battery:
[0041] The active material, binder and conductive agent are coated in a ratio of 8:1:1, placed in a vacuum oven and kept at 120°C for 6 hours for drying and cut into pieces to obtain lithium iron phosphate pole pieces, and the Tp-BD-COF diaphragm and lithium iron phosphate pole pieces prepared in step 2) are assembled in a button battery to obtain a lithium ion battery; wherein the active material is lithium iron phosphate, the binder is polyvinylidene fluoride, and the conductive agent is carbon black.
[0042] 4) Test the performance of button batteries.
[0043] The button cell assembled in step 3) was tested for specific capacity, and the specific capacity of the button cell was 142 mAh / g.
[0044] Example 2
[0045] A method for preparing a wide temperature range lithium-ion battery separator comprises the following steps:
[0046] 1) Preparation of covalent organic framework material Tp-BD-COF:
[0047] 0.01mmol of trialdehyde phloroglucinol and 0.15mmol of benzidine were weighed into an ampoule tube, and 2ml of anisole and 0.2ml of acetic acid solution were added in sequence. The ampoule tube was degassed by freeze-thaw cycles for 3 times under liquid nitrogen environment. The ampoule tube was sealed and placed in a constant temperature oven at 120℃ for 96h to obtain an orange covalent organic framework material Tp-BD-COF. Figure 1 This is the structural diagram of the prepared covalent organic framework material Tp-BD-COF, wherein the concentration of the acetic acid solution is 12 mol / L;
[0048] 2) Preparation of Tp-BD-COF membrane:
[0049] The covalent organic framework material Tp-BD-COF prepared in step 1) is placed at 120° C. for 12 hours for activation to obtain activated Tp-BD-COF;
[0050] Weigh 9 mg of activated Tp-BD-COF and 1 mg of PE and grind them evenly. Grind the white PE particles and the orange-yellow activated Tp-BD-COF until there is no obvious granularity, then add 1 mg of liquid paraffin and mix well. Place the mixed material at 150°C until the PE melts and then stand for 20-30 seconds. Take it out after the mixture is formed.
[0051] The mixture was placed on a roller press and the temperature was controlled at 112°C to roll to a 25 μm thick membrane. The membrane was then rolled five times to soak in dichloromethane for 12 hours to remove the liquid paraffin. The membrane was then placed in a 60°C oven for 1 hour to dry to remove the dichloromethane. Finally, the membrane was cut into 9 mm round membranes using a cutting machine to obtain a Tp-BD-COF membrane. Figure 3 , the mass is 10-14 mg; the roller pressing method is simple and the process flow is convenient;
[0052] 3) Assemble the button battery:
[0053] The active material, binder and conductive agent are coated in a ratio of 8:1:1, placed in a vacuum oven and kept at 120°C for 6 hours for drying and cut into pieces to obtain lithium iron phosphate pole pieces, and the Tp-BD-COF diaphragm and lithium iron phosphate pole pieces prepared in step 2) are assembled in a button battery to obtain a lithium ion battery; wherein the active material is lithium iron phosphate, the binder is polyvinylidene fluoride, and the conductive agent is carbon black.
[0054] 4) Test the performance of button batteries.
[0055] The button cell assembled in step 3) was tested for specific capacity, and the specific capacity of the button cell was 121 mAh / g.
[0056] Example 3
[0057] A method for preparing a wide temperature range lithium-ion battery separator comprises the following steps:
[0058] 1) Preparation of covalent organic framework material Tp-BD-COF:
[0059] 0.01mmol of trialdehyde phloroglucinol and 0.15mmol of benzidine were weighed into an ampoule tube, and 2ml of anisole and 0.2ml of acetic acid solution were added in sequence. The ampoule tube was degassed by freeze-thaw cycles for 3 times under liquid nitrogen environment. The ampoule tube was sealed and placed in a constant temperature oven at 120℃ for 96h to obtain an orange covalent organic framework material Tp-BD-COF. Figure 1 This is the structural diagram of the prepared covalent organic framework material Tp-BD-COF, wherein the concentration of the acetic acid solution is 12 mol / L;
[0060] 2) Preparation of Tp-BD-COF membrane:
[0061] The covalent organic framework material Tp-BD-COF prepared in step 1) is placed at 120° C. for 12 hours for activation to obtain activated Tp-BD-COF;
[0062] Weigh 8 mg of activated Tp-BD-COF and 2 mg of PE and grind them evenly. Grind the white PE particles and the orange-yellow activated Tp-BD-COF until there is no obvious granularity, then add 1 mg of liquid paraffin and mix well. Place the mixed material at 150°C until the PE melts and then stand for 20-30 seconds. Take it out after the mixture is formed.
[0063] The mixture was placed on a roller press and the temperature was controlled at 112°C to roll to a 25 μm thick membrane. The membrane was then rolled five times to soak in dichloromethane for 12 hours to remove the liquid paraffin. The membrane was then placed in a 60°C oven for 1 hour to dry to remove the dichloromethane. Finally, the membrane was cut into 9 mm round membranes using a cutting machine to obtain a Tp-BD-COF membrane. Figure 3 , the mass is 10-14 mg; the roller pressing method is simple and the process flow is convenient;
[0064] 3) Assemble the button battery:
[0065] The active material, binder and conductive agent are coated in a ratio of 8:1:1, placed in a vacuum oven and kept at 120°C for 6 hours for drying and cut into pieces to obtain lithium iron phosphate pole pieces, and the Tp-BD-COF diaphragm and lithium iron phosphate pole pieces prepared in step 2) are assembled in a button battery to obtain a lithium ion battery; wherein the active material is lithium iron phosphate, the binder is polyvinylidene fluoride, and the conductive agent is carbon black.
[0066] 4) Test the performance of button batteries.
[0067] The button battery assembled in step 3) was tested for specific capacity. The specific capacity of the button battery was 151 mAh / g. Compared with the first two groups of embodiments, it can be clearly concluded that the button battery assembled with the Tp-BD-COF membrane prepared when the mass ratio of activated Tp-BD-COF, PE and liquid paraffin was 8:2:1 had the largest specific capacity.
[0068] The performance of the Tp-BD-COF separator prepared with the mass ratio of activated Tp-BD-COF, PE and liquid paraffin at 8:2:1 and the assembled button battery was compared with that of the commercial PP separator. Figure 2 It can be seen that there is a peak in the X-ray powder diffraction pattern of the Tp-BD-COF membrane, and there is no interference from other miscellaneous peaks, so the Tp-BD-COF membrane has good crystallinity; Figure 4 The conductivity and conductivity derivative of the Tp-BD-COF membrane prepared with the mass ratio of activated Tp-BD-COF, PE and liquid paraffin being 8:2:1 and the commercial PP membrane are shown in Table 1. Figure 4 It can be seen that the conductivity of Tp-BD-COF separator at the same temperature of 20℃, 0℃ and -10℃ is better than that of commercial PP separator. Figure 5 It can be seen that the button battery assembled with the Tp-BD-COF separator prepared with a mass ratio of 8:2:1 after activation of Tp-BD-COF, PE and liquid paraffin can show normal charge and discharge curves from -30℃ to 20℃, indicating that the button battery can be charged and discharged normally from -30℃ to 20℃; Figure 6 The left figure shows the specific capacity of a button cell assembled with a Tp-BD-COF separator prepared with a mass ratio of 8:2:1 among activated Tp-BD-COF, PE and liquid paraffin, and a button cell assembled with a commercial PP separator measured at 25°C. Figure 6 The right figure shows the specific capacity of a button cell assembled with a Tp-BD-COF separator prepared with a mass ratio of 8:2:1 for activated Tp-BD-COF, PE and liquid paraffin, and a button cell assembled with a commercial PP separator measured at -20°C. Figure 6It can be seen that the specific capacity of the button battery assembled with Tp-BD-COF separator is better than the specific capacity of the button battery assembled with commercial PP separator, whether at 25℃ or -20℃.
[0069] The invention prepares a Tp-BD-COF diaphragm from a covalent organic framework material Tp-BD-COF and PE by a roll pressing method and applies the diaphragm to the field of lithium ion battery diaphragms. The roll pressing method is simple in preparation and convenient in process flow. The pore effect of the covalent organic framework material Tp-BD-COF is used to prepare a diaphragm with good ion conductivity. A button battery assembled using the Tp-BD-COF diaphragm has a stable charge and discharge curve and still has good performance at low temperature compared to a commercial PP diaphragm. The conductivity and the specific capacity of the assembled battery in a wide temperature range are both better than those of the commercial PP diaphragm, the safety performance is high, and large-scale production is easy.
[0070] The above describes in detail the implementation modes of the present invention in conjunction with the accompanying drawings, but the present invention is not limited to the above implementation modes. The implementation modes can still be changed within the knowledge scope of ordinary technicians in the field. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a wide temperature range lithium ion battery separator, characterized in that: The following steps are involved: 1) Preparation of covalent organic framework material Tp-BD-COF; 2) Preparation of Tp-BD-COF membrane: The covalent organic framework material Tp-BD-COF prepared in step 1) is placed at 120° C. for 12 hours for activation to obtain activated Tp-BD-COF; Weigh the activated Tp-BD-COF and PE and grind them evenly, then continue to add liquid paraffin and mix well; place the mixed materials at 140-160°C until PE melts and then stand for 20-30 seconds, and take them out after the mixture is formed; The mixture was placed on a roller press and the temperature was controlled at 110-115° C. to roll into a diaphragm with a thickness of 10-40 μm, the diaphragm was immersed in dichloromethane for 12 hours, and then the diaphragm was placed in a 60° C. oven for drying, and finally the diaphragm was cut into a circular diaphragm using a cutting machine to obtain a Tp-BD-COF diaphragm; 3) Assemble button batteries; 4) Test the performance of button batteries.
2. The method for preparing a wide temperature range lithium-ion battery separator according to claim 1, characterized in that: The step of preparing the covalent organic framework material Tp-BD-COF in step 1) is as follows: weighing trialdehyde phloroglucinol and benzidine into an ampoule tube and sequentially adding anisole and acetic acid solution, degassing by freeze-thaw cycle in a liquid nitrogen environment, sealing the ampoule tube and placing it in a constant temperature oven at 110-130° C. to react for 90-100 hours to obtain the covalent organic framework material Tp-BD-COF.
3. The method for preparing a wide temperature range lithium ion battery separator according to claim 2, characterized in that: In the step 1), the molar ratio of trialdehyde phloroglucinol, benzidine, anisole and acetic acid solution is 0.05-0.2: 0.075-0.3: 1.5-3: 0.1-0.
3.
4. The method for preparing a wide temperature range lithium-ion battery separator according to claim 3, characterized in that: The concentration of the acetic acid solution in step 1) is 12 mol / L.
5. The method for preparing a wide temperature range lithium-ion battery separator according to claim 4, characterized in that: In the step 2), the mass ratio of activated Tp-BD-COF, PE and liquid paraffin is 5-9:1-5:
1.
6. The method for preparing a wide temperature range lithium-ion battery separator according to claim 5, characterized in that: The mass ratio of activated Tp-BD-COF, PE and liquid paraffin in the step 2) is 8:2:
1.
7. The method for preparing a wide temperature range lithium-ion battery separator according to claim 6, characterized in that: In the step 2), the temperature of PE when melted is controlled at 150° C., and the temperature of the roller press is controlled at 112° C. and the roller press is performed five times to form a diaphragm with a thickness of 25 μm.
8. The method for preparing a wide temperature range lithium-ion battery separator according to claim 7, characterized in that: The diameter of the circular diaphragm in step 2) is 9 mm.
9. The method for preparing a wide temperature range lithium-ion battery separator according to claim 8, characterized in that: The step of assembling the button battery in step 3) is as follows: coating the active material, the binder and the conductive agent in a ratio of 8:1:1, placing in a vacuum oven to dry at 100-140°C and cutting to obtain lithium iron phosphate pole pieces, assembling the Tp-BD-COF diaphragm and the lithium iron phosphate pole pieces obtained in step 2) in the button battery to obtain a lithium ion battery.
10. The method for preparing a wide temperature range lithium-ion battery separator according to claim 9, characterized in that: In the step 3), the active material is lithium iron phosphate, the binder is polyvinylidene fluoride, and the conductive agent is carbon black.
Citation Information
Cited By
Piezoelectric self-adaptive diaphragm as well as preparation method and application thereof
CN121688350A
